2013
DOI: 10.1007/s13191-013-0283-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Marginal and Internal Gap of Co–Cr Copings Fabricated from Conventional Wax Pattern, 3D Printed Resin Pattern and DMLS Tech: An In Vitro Study

Abstract: Accuracy of the fit of the restoration has always remained as one of the primary factors in determining success of the restoration. A well fitting restoration needs to be accurate both along its margins and internal surface. This study was conducted to comparatively evaluate the marginal gap and internal gap of cobalt-chromium (Co-Cr) copings fabricated by conventional casting procedures and with direct metal laser sintering (DMLS) technique. Among the total of 30 test samples 10 cast copings were made from in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 31 publications
2
39
0
Order By: Relevance
“…The programmed die spacer thickness for CAD/Cercon was 10 to 20 μm and CAD/Cerec was -100 μm; the average internal gaps obtained were 100 to 130 μm for CAD/Cercon and 60 to 70 μm for CAD/Cerec. In contrast, Bhaskaran et al 26 reported on the marginal and internal gap of Co-Cr copings cast from 3D printed resin patterns to be 27.22 μm and 36.15 μm. In this study, the mean measured internal gaps of the group of 25 μm was 3 times greater than the programmed die spacer thickness value (25 μm).…”
mentioning
confidence: 90%
“…The programmed die spacer thickness for CAD/Cercon was 10 to 20 μm and CAD/Cerec was -100 μm; the average internal gaps obtained were 100 to 130 μm for CAD/Cercon and 60 to 70 μm for CAD/Cerec. In contrast, Bhaskaran et al 26 reported on the marginal and internal gap of Co-Cr copings cast from 3D printed resin patterns to be 27.22 μm and 36.15 μm. In this study, the mean measured internal gaps of the group of 25 μm was 3 times greater than the programmed die spacer thickness value (25 μm).…”
mentioning
confidence: 90%
“…37 In the literature, different in vitro and in vivo studies investigated the fitting accuracy of crowns and evaluated a marginal gap between 10 and 190 µm as an acceptable clinical range. 4,38 For example, Bhaskaran et al 38 investigated a clinically acceptable gap between 10 and 160 µm for the marginal gap and 81 and 136 µm for the internal gap. Vojdani et al 19 also investigated the new system Ceramill Sintron with presintered Co-Cr restorations and showed 195 µm for the mean marginal discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…Literature suggest a range of accepted marginal gaps, from 120 µm suggested by Mclean and von Fraunhoder to 100 µm. In other studies accepted marginal gap varies between 10 µm and 160 µm and internal gap between 81 µm and 136 µm [3,14].…”
mentioning
confidence: 97%
“…A ceramic material is applied on a metal framework using a multi-layer sintering process or overpressing the porcelain [1].Conventional lost-wax technique and casting is the most used technique in producing fixed dental restorations and its advantages and long-term success has been proved. But this procedure is also very technique-sensitive, and wax patterns are fragile, prone to distortions, thermal sensitive, have high coefficient of thermal expansion and elastic memory [2,3]. Other methods to obtain patterns imply self-curing or light-curing resins to exceed shortcomings of wax-patterns, producing stable and precise pieces.…”
mentioning
confidence: 99%
See 1 more Smart Citation